The Influence Of Price Perception And Brand Image On Repurchase Intention Among Street Vendors - Ahmad Saputra; Muhammad Bintang; Ahmad Nuh (Interkoneksi: Journal of Computer Science and Digital Business, 2024)
This study focuses on analyzing the effect of price perception and brand image on street vendors' repurchase intentions. In this study, street vendors are considered as subjects who play an important role in influencing consumer repurchase decisions for a product. The results showed that price perception has no significant effect on repurchase intention, but brand image has a positive and significant effect on repurchase intention. This means that street vendors who have a good brand image and are seen as a trustworthy brand can increase consumer repurchase intentions. Therefore, this study provides a strategy to increase consumer repurchase intentions by developing a positive and meaningful brand image.